Factors influencing behavior in the forced swim test - Bogdanova, Olena V. (Physiol Behav, 2013)
The forced swim test (FST) is a behavioral test in rodents which was developed in 1978 by Porsolt and colleagues as a model for predicting the clinical efficacy of antidepressant drugs. A modified version of the FST added the classification of active behaviors into swimming and climbing, in order to facilitate the differentiation between serotonergic and noradrenergic classes of antidepressant drugs. The FST is now widely used in basic research and the pharmaceutical screening of potential antidepressant treatments. It is also one of the most commonly used tests to assess depressive-like behavior in animal models. Despite the simplicity and sensitivity of the FST procedure, important differences even in baseline immobility rates have been reported between different groups, which complicate the comparison of results across studies. In spite of several methodological papers and reviews published on the FST, the need still exists for clarification of factors which can influence the procedure. While most recent reviews have focused on antidepressant effects observed with the FST, this one considers the methodological aspects of the procedure, aiming to summarize issues beyond antidepressant action in the FST. The previously published literature is analyzed for factors which are known to influence animal behavior in the FST. These include biological factors, such as strain, age, body weight, gender and individual differences between animals; influence of preconditioning before the FST: handling, social isolation or enriched environment, food manipulations, various kinds of stress, endocrine manipulations and surgery; schedule and routes of treatment, dosage and type of the drugs as well as experimental design and laboratory environmental effects. Consideration of these factors in planning experiments may result in more consistent FST results.